Effect of TetR Family Transcriptional Regulator PccD on Phytosterol Metabolism of Mycolicibacterium - Peiyao Xiao; Delong Pan; Fuyi Li; Yuying Liu; Yang Huang; Xiuling Zhou; Yang Zhang (Microorganisms)
Androstenedione (AD) is an important intermediate for the production of steroidal drugs. The process of transforming phytosterols into AD by Mycolicibacterium is mainly the degradation process of the phytosterol side chain, and the excessive accumulation of propionyl-CoA produced by Mycobacterium will produce toxic effects, which seriously restricts the transformation performance of strains. In this study, Mycolicibacterium sp. LZ2 (Msp) was used as the research object to study the transcription factor PccD of the TetR family, which has the role of propionyl-CoA metabolism regulation. By constructing overexpression and deletion strains of pccD, it was confirmed that pccD had an inhibitory effect on the transcription of propionyl-CoA carboxylase genes (pccA and pccB). Electrophoretic Mobility Shift Assay (EMSA) and DNase I footprint analysis demonstrated that PccD is directly involved in the transcriptional regulation of pccA and pccB and is a negative transcriptional regulator of the pcc operon. In the study of phytosterol transformation, the growth rate and bacterial viability of Msp-ΔpccD were higher than Msp, but the growth of Msp-pccD was inhibited. As a result of testing of intracellular propionyl-CoA levels and AD production yields, it was found that lower propionyl-CoA levels and higher AD production yields were observed in Msp-ΔpccD. The results expand the cognition of propionyl-CoA metabolism regulation and provide a theoretical basis and reference for the rational transformation of phytosterol transformation strains and secondary metabolite synthesis strains with propionyl-CoA as a substrate, which has important research significance.